Tarjamah al-Qur'an al-Karim ila al-Lughah al-Ajnabiyyah wa Ishkaliyatuha - Endang Saeful Anwar (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2011)
ولقد جاءت كلمة